2020
DOI: 10.1007/s00167-020-06246-4
|View full text |Cite
|
Sign up to set email alerts
|

Correction of severe valgus osteoarthritis by total knee arthroplasty is associated with increased postoperative ankle symptoms

Abstract: The aim of this study was to assess the mid-term clinical outcome of the ankle joint after total knee arthroplasty (TKA) in high-grade valgus osteoarthritis. Methods In this case-control study, n = 36 patients with a preoperative mechanical tibiofemoral angle (mTFA) ≥ 15° who underwent TKA between December 2002 and December 2012 were included. The control group (mTFA < 15°) of n = 60 patients was created using case matching. Radiological [mechanical tibiofemoral angle (mTFA) and ankle joint orientation to the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Enough range of motion in this region might not be given in patients with an ankle arthrodesis by a nail. In patients with indication for osteotomy around the knee and primary or secondary arthritis of the ankle joints, we would recommend performing the osteotomy around the knee first and then treat the ankle afterwards-especially when indicating ankle arthrodesis [22][23][24][25][26][27]. With this sequence of surgeries, the surgeon can sustainably accomplish a correct foot position when performing the ankle arthrodesis.…”
Section: Discussionmentioning
confidence: 99%
“…Enough range of motion in this region might not be given in patients with an ankle arthrodesis by a nail. In patients with indication for osteotomy around the knee and primary or secondary arthritis of the ankle joints, we would recommend performing the osteotomy around the knee first and then treat the ankle afterwards-especially when indicating ankle arthrodesis [22][23][24][25][26][27]. With this sequence of surgeries, the surgeon can sustainably accomplish a correct foot position when performing the ankle arthrodesis.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported on increased pain and impaired function of the ankle joint following TKA, particularly in high-grade varus or valgus knee osteoarthritis when the mechanical axis was corrected beyond > 10-15° [5][6][7][8]. But these studies could not clarify whether TKA leads to the onset or progression of ankle pain or if the ankle pain had already been present but was masked by symptoms of knee osteoarthritis.…”
Section: Discussionmentioning
confidence: 98%
“…Mechanical corrections performed on a single joint can have vast implications for neighbouring joints, as well [4]. Recently, clinical studies reported that following total knee arthroplasty (TKA), patients may develop ankle symptoms, particularly if patients had an excessive pre-operative varus or valgus malalignment [5][6][7][8]. It is necessary to identify the mechanisms of the ankle and knee joint mutually affecting each other-both pre-operatively in knee osteoarthritis and following TKA.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 8 This is also relevant in the field of joint arthroplasty that involves alteration of the alignment of the knee. 19 , 20 …”
Section: Discussionmentioning
confidence: 99%